Analisis Korelasi Kualitas Free-Body Diagram dan Penguasaan Konsep Siswa Pada Materi Dinamika - Ogi Danika Pranata (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2024)
The goal of learning physics is not to memorize the formulas or equations, but to increase conceptual understanding. For increase conceptual understanding about motion, force analysis skill is the most fundamental skills needed by students. Free-body diagram will help students to analyze force. So this study aims to determine and analyze the correlation between quality of free-body diagrams and mastery of dynamics concepts. The research was conducted at SMAN 2 Sungai Penuh. The population is students of XI MIA. Using whole population sampling, 50 students. The learning process and tests on dynamics were to gather the data about quality of free-body diagram and concept understanding. Both data was normally distributed and linearly related with a positive correlation shown by a scatterplot. The Pearson correlation test conducted to show the relationship between variables. There was high correlation between the quality of free-body diagrams and conceptual understanding as indicated by the Pearson correlation coefficient . The correlation was highly positive, which means that students who draw high quality free-body diagram tend to have high conceptual understanding.